Pendampingan Pembelajaran Penulisan Arab Pegon bagi Santri Pondok Pesantren Darul Fawaid Ilmiyah Randujalak Besuk Probolinggo - Sulton Firdaus; Bintang Ramadhan (Yayasan Literasi Altruis Khatulistiwa, 2025)
The Arabic Pegon literacy learning plays a crucial role in preserving Islamic literacy traditions within Islamic boarding schools (pesantren), especially among students studying classical Islamic texts (kitab kuning). However, many new students lack a basic understanding of proper Pegon writing, resulting in low reading competence and decreased learning motivation. This community service program aims to improve the ability of students at Darul Fawaid Ilmiyah Islamic Boarding School, Randujalak Village, Besuk District, Probolinggo Regency, in understanding and writing Arabic Pegon. The method used is intensive mentoring and practice-based training (learning by doing) through four stages: initial observation, regular tutoring, micro teaching for teachers, and learning evaluation. The results show a significant improvement in students’ motivation and writing skills, with an average post-test score increase of 35% compared to the pre-test. Furthermore, teacher training positively affected teaching professionalism, particularly in material preparation and classroom management. This program recommends integrating Arabic Pegon learning into the regular pesantren curriculum and conducting continuous teacher training to strengthen the Pegon literacy ecosystem within Islamic educational institutions